ANALISIS PENGEMBANGAN BANDAR UDARA INTERNASIONAL SOEKARNO HATTA–JAKARTA - JB. PURWADI (Politeknik Penerbangan Indonesia Curug, 2012)
The airport development planning must consider two main characteristics of the local economy that the airport needs for transportation and land requirements for the development of housing for residents around the airport, in order to get a new job. So the airport planning must be done in accordance with the comprehensive regional plan. Based on the analysis states that in order to cope with increasing passenger and aircraft movement in 2030 must be changing the layout of the Soekarno-Hatta airport facilities. To cope with increasing passenger and aircraft movement, the necessary expansion of the terminal building area of 232,964 m2, making the 1 (one) new runway, so entirely into 3 (three) pieces of the runway and the addition and expansion of apron. For its realization has been prepared by PT (Persero) Angkasa Pura II in the form of Grand Design Soekarno-Hatta Airport 2011.